2011
DOI: 10.1371/journal.pone.0026689
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Artesunate on Parasite Recrudescence and Dormancy in the Rodent Malaria Model Plasmodium vinckei

Abstract: Artemisinin (ART) is the recommended first line therapy for treating uncomplicated and drug-resistant Plasmodium falciparum, the most pathogenic form of malaria. However, treatment failure following ART monotherapy is not uncommon and resistance to this rapidly acting drug has been reported in the Thai-Cambodian border. Recent in vitro studies have shown that following treatment with dihydroartemisinin (DHA), the development of ring-stage parasites is arrested for up to 20 days. These arrested (i.e. dormant) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 28 publications
5
56
0
2
Order By: Relevance
“…This problem is observed during the long-term treatment of malaria (Lacrue et al, 2011). Moreover, similar antiplasmodial studies suggested that follow-up of mice for at least 1 month becomes necessary in order to monitor the efficacy of any antimalarial drug (Rajendran et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This problem is observed during the long-term treatment of malaria (Lacrue et al, 2011). Moreover, similar antiplasmodial studies suggested that follow-up of mice for at least 1 month becomes necessary in order to monitor the efficacy of any antimalarial drug (Rajendran et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there remains an urgent need to develop new antimalarials [6]. However, the behaviour of current artemisinins is still not fully understood; debate remains concerning their mechanism of action [7,8] and stage-specific effects [9]. One theory is that artemisinins decompose when activated by iron that has accumulated in malaria infected red blood cells, forming free radicals which then damage the parasites [10].…”
Section: Introduction E15mentioning
confidence: 99%
“…This recrudescence may be attributed to either resistant or arrested/dormant parasites, or the drug concentrations in blood falling below their effective levels, but such issues have not yet been fully characterised [9].…”
Section: Introduction E15mentioning
confidence: 99%
“…Artemisinin and its derivatives have been used as antimalarials with increasing frequency since the 1990s [3]. They are the most rapidly acting drugs out of the currently available anti-malarials [4], reducing the parasite biomass ∼10, 000-fold However, the behaviour of current artemisinins is still not fully understood; debate remains concerning their mechanism of action [7,8] and stage-specific effects [9]. One theory is that artemisinins decompose when activated by iron that has accumulated in malaria infected red blood cells, forming free radicals which then damage the parasites [10].…”
Section: Introductionmentioning
confidence: 99%
“…
c o m p u t e r m e t h o d s a n d p r o g r a m s i n b i o m e d i c i n e 1 1 2 ( 2 0 1 3 ) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] j o u r n a l h o m e p a g e : w w w . i n t l .
…”
unclassified